Jurisprudence-Legal Consideration of Lab Children’s Marriage whit their Parents in Compare to Adopted Child’s Marriage with Guardian - Mahmoodian, Nazli; Abbasi, Mahmoud; Aganavesi, Marjan (Bioethics and Health Law Journal (BHL), 2026)
The rapid advancements in Assisted Reproductive Technologies (ART) introduce novel ethical and jurisprudential dilemmas distinct from traditional adoption practices, particularly concerning marital law. This study aims to address the core research question: What is the comparative legal ruling, based on Islamic jurisprudence and civil law, on the permissibility of marriage between children conceived via ART and gamete owners, in contrast to adopted children and their legal guardians? The central hypothesis posits that the presence of a direct genetic link in ART cases fundamentally prohibits marriage (akin to consanguinity), whereas the absence of such a link in adoption necessitates only legal ratification based on child welfare, despite psychological concerns. The research utilizes a doctrinal-comparative analytical framework to examine classifications based on gamete origin (own, donated or surrogacy) and contrasts these findings with the lineage and marriage barriers inherent in adoption. This research adopts an applied, theoretical approach situated within the field of Theology and comparative Family Law; thus, no empirical data collection was undertaken. The primary methodology employed was doctrinal and comparative analysis. The doctrinal method was utilized to systematically categorize and evaluate the permissibility of marriage concerning ART-conceived children based on the established Islamic legal principles governing lineage and gamete ownership across the four identified scenarios (own gametes, sperm donation, oocyte donation and surrogacy). This was further strengthened by a comparative legal framework, juxtaposing the findings derived from the genetic connections in ART with the established legal and welfare considerations governing adoption. This dual-framework approach ensures methodological validity by grounding conclusions in both deep jurisprudential exploration and cross-legal comparison. Results confirm that genetic attribution in ART mandates prohibition of marriage for all related parties, including surrogate mothers. Conversely, while adoption has no biological barrier to marriage, legal and psychological advisability remains the primary regulatory concern. This paper concludes that although genetic linkage, not mere custodial relationship, is the defining criterion for prohibiting marriage under current jurisprudential and legal norms but, legal frameworks in many jurisdictions, including Iran, require specific permissions from religious authorities and courts, prioritizing the child’s welfare. Despite the legal possibility, there is a significant consensus among psychologists and legal experts that marriage between an adopted child and their guardian is inadvisable and potentially harmful.